Peranan Silahturahmi Terhadap Kesuksesan Berwirausaha Alumni Akademi Kesejahteraan Sosial AKK Yogyakarta - Ms Istiqomah (Akademi Kesejahteraan Sosial AKK Yogyakarta, 2020)
This research aims to determine the role of relationship with the success of entrepreneurial students of AKS-AKK Yogyakarta. Method used using a descriptive qualitative method. This research will research aimed at obtaining a complete picture of a matter according to the human view that is researched, the role of relationship. Research subject by student alumni at AKK Social Welfare Academy who have been entrepreneurial. Data retrieval with interview methods conducted in September 2019. Sampling in this study amounted to 3 students of ALUMNI study Program graduating in the year 2018. The instrument used is by using interview guidelines. Data analysis technique used is the analysis of the quality data is done interactively and lasts continuously until complete, so the data has been saturated. The results of this study showed that the success factor of the business is about the activities of the relationship stating that the three respondents always do the relationship, either in the place of relatives, friends, or neighbours. Another statement affirmed that the relationship will be very beneficial to the business they are living in, with the friendship will help market the products that are owned. The form of relationship to provide benefits to the business, among others, with an activity such as study or artisan, play activities together, or deliberately by visiting activities to strengthen the relationship. The results of this research concluded that there is a family environment influence on entrepreneurial interest in AKS students – AKK Yogyakarta.